Resveratrol prevents high-calorie diet-induced learning and memory dysfunction in juvenile C57BL/6J mice. (3rd August 2018) - Xu, Bao-Lei; Zhang, Hui; Ma, Li-Na; Dong, Wen; Zhao, Zhi-Wei; Zhang, Jing-Shuang; Wang, Yu-Lan; Zhang, Xu; Wang, Rong
ABSTRACT: Objective : Because resveratrol (RSV) has been shown to improve learning and memory, so we investigated the potential benefit of RSV on learning and memory deficits in juvenile mice fed with a HC diet and explored the molecular mechanisms underlying this process. Methods : Six-week-old C57BL/6J mice were divided into three different diet groups: control, HC diet, and HC + RSV diet. Serum insulin and insulin-like growth factor 1 (IGF-1) levels were measured using enzyme-linked immunosorbent assays. Protein expression was examined by immunohistochemistry and western blotting. Results : Administration of RSV daily (30 mg/kg) prevented the HC diet-induced increase in juvenile animal body weight but did not improve any other physiological conditions, including fasting blood glucose and serum cholesterol, triglyceride, insulin, and IGF-1 levels. However, RSV did prevent learning and memory deficits in the HC group. Peroxisome proliferator-activated receptor gamma (PPARγ) was downregulated in the CA1 region of the hippocampus in both the HC and HC + RSV groups, but the reduction was significantly greater in the HC + RSV group ( P < .01 compared with the HC group). Moreover, although the HC diet reduced the number of p16-positive neurons, the HC + RSV diet significantly upregulated p16 expression in the CA1 region of the hippocampus ( P < .01 compared with the HC group). Conclusions : RSV protected against learning and memory impairments in juvenile animals fed with a HC diet, possibly via upregulation of p16 or downregulation of PPARγ in the hippocampal CA1 region.